Maltose-bis(hydroxymethyl)phenol (MBPs) and Maltosetris(hydroxymethyl)phenol (MTPs) Amphiphiles for Membrane Protein Stability - Ehsan,M; Wang,H; Cecchetti,C; Mortensen,JS; Du,Y; Hariharan,P; Nygaard,A; Lee,HJ; Ghani,L; Guan,L; Loland,CJ; Byrne,B; et al. (ACS Chemical Biology, 2021)
Membrane protein structures provide a fundamental understanding of their molecular actions and are of importance for drug development. Detergents are widely used to solubilize, stabilize, and crystallize membrane proteins, but membrane proteins solubilized in conventional detergents are prone to denaturation and aggregation. Thus, developing novel detergents with enhanced efficacy for protein stabilization remains important. We report herein the design and synthesis of a class of phenol-derived maltoside detergents. Using two different linkers, we prepared two sets of new detergents, designated maltose-bis(hydroxymethyl)phenol (MBPs) and maltose-tris(hydroxymethyl)phenol (MTPs). The evaluation of these detergents with three transporters and two G-protein coupled receptors allowed us to identify a couple of new detergents (MBP-C9 and MTP-C12) that consistently conferred enhanced stability to all tested proteins compared to a gold standard detergent (DDM). Furthermore, the data analysis based on the detergent structures provides key detergent features responsible for membrane protein stabilization that together will facilitate the future design of novel detergents.